Axonal membrane trafficking regulation and its failure in cargo delivery - Chaiamarit, T (2023)
Regulation of axonal trafficking of membrane-bound compartments is important for delivery of various neuronal cargoes towards the distal synapses and for quality control of damaged cellular components/toxic proteins. The contribution of Rab GTPase pathways in neurodegenerative pathologies and the regulatory mechanism to replenish various Rab proteins in the axonal periphery remain unclear. In the Encalada lab, we modeled familial prion disease axonopathies in primary murine hippocampal neurons, to determine (1) the biogenesis pathway that forms neurotoxic mutant prion protein (PrPmut) aggregates and (2) the consequences of PrPmut aggregate formation on cytoskeletal-organelle interactions within swollen axons that PrPmut aggregates reside. Firstly, I, and the research team, identified that the small GTPase ARL8 recruits kinesin-1 and HOPS for axonal transport and fusion, respectively, that generates neurotoxic PrPmut aggregates in non-degradative endolysosomes, called ‘endoggresomes.’ This axonal rapid endosomal sorting and transport-dependent aggregation (ARESTA) mechanism forms endoggresomes rapidly, and as a result impair calcium dynamics and neuronal viability. Inhibition of ARESTA reduces axonal endoggresome densities and rescues neuronal dysfunction, providing an anti-aggregation target to ameliorate prionopathies. Secondly, axonal micro-domain analysis of live organelle dynamics within endoggresome sites showed deficits to the MT-based active transport system, that result in enhanced mitochondrial-Rab7 endosomal contacts that induce mitochondrial fission via Rab7 activity and render retained mitochondria dysfunctional. In the Davis lab, I studied post-transcriptional fate of rab GTPase mRNA towards their axonal localization and function at the Drosophila larval neuromuscular junction (NMJ) pre-synapse. I found that a conserved RNA-binding protein Imp and kinesin-1 are required for rab11 mRNA delivery to axon termini and are required for synaptic plasticity and unimpaired locomotory behavior. Furthermore, I detected transcripts of multiple important rab GTPases for endosome recycling at the axonal and glial periphery at the NMJ, uncovering an unorthodox regulatory mechanism of axonal membrane trafficking.